When is high-dose intravenous iron repletion needed? Assessing new treatment options - David Gozzard (Dove Medical Press, 2011)
David GozzardBetsi Cadwaladr University Health Board, Llandudno, Wales, UKAbstract: High doses of intravenous iron have a role in the treatment of a number of clinical situations associated with iron deficiency, iron deficiency anemia, and blood loss. In the presence of functioning erythropoiesis, iron supplementation alone may be adequate to replenish iron stores and restore blood loss. Where hormone replacement with an erythropoiesis-stimulating agent is required, iron adequacy will optimize treatment. Intravenous iron offers a rapid means of iron repletion and is superior to oral iron in many circumstances, especially in the presence of anemia of chronic disease, where it appears to overcome the block to absorption of iron from the gastrointestinal tract and immobilization of stored iron. The clinical situations where high doses of iron are commonly required are reviewed. These include nondialysis-dependent chronic kidney disease, inflammatory bowel disease, obstetrics, menorrhagia, and anemia associated with cancer and its treatment. The literature indicates that high doses of iron are required, with levels of 1500 mg in nondialysis-dependent chronic kidney disease and up to 3600 mg in inflammatory bowel disease. New formulations of intravenous iron have recently been introduced that allow clinicians to administer high doses of iron in a single administration. Ferumoxytol is available in the US, has a maximum dose of 510 mg iron in a single administration, but is limited to use in chronic kidney disease. Ferric carboxymaltose can be rapidly administered in doses of 15 mg/kg body weight, up to a ceiling dose of 1000 mg. A test dose is not required, and it can be used more widely across a spectrum of iron deficiency and iron deficiency anemia indications. The latest introduction is iron isomaltoside 1000. Again, a test dose is not required, and it can be delivered rapidly as an infusion (in an hour), allowing even higher doses of iron to be administered in a single infusion, ie, 20 mg/kg body weight with no ceiling. This will allow clinicians to achieve high-dose repletion more frequently as a single administration. Treatment options for iron repletion have taken a major leap forward in the past two years, especially to meet the demand for high doses given as a single administration.Keywords: iron isomaltoside 1000, intravenous iron, iron deficiency anemia, iron deficiency, high dose, single dose, erythropoiesis